Personal navigator for visual impaired person utilizing galvanic vestibular stimulator - Md Sarif, Nur Azhani (2013)
Electronic industry is growing fast by introducing new product and technology to the society. The technology helps to enhance human daily life by promoting easy and modern life. However, the development of technology does not contribute that much to less fortunate communities. Visual impaired person have difficulties to navigate in an unfamiliar destination without any help. Introducing galvanic vestibular stimulation (GVS) can help them to navigate the desired destination. However, technology of GVS is still under development. GVS is a device that delivered small value of current to the vestibular system through electrodes placed over the mastoid area. Thus, investigation of GVS on human is needed to improve the reliability of the system. It is very helpful if an impaired person can have a GVS device that can be attach to them to help them during navigation. A coordinator is used to control the test subject movement wirelessly. In order to allow the movement, human equilibrium has to be adjusted. Due to the fact that vestibular system is the one that control human equilibrium, thus, current is injected at the back of ear using an electrode to allow disturbance to human equilibrium and effect body posture. The magnitude of the movement is control based on intensity of current injected. The result suggests that as intensity scale of current injected is increased from 0% to 100%, deflections angle of the test subject will increase from 0 up to 47%. However, different test subjects will have different range of degree depending on their body resistance. One of the findings in the research prove that when the same magnitude of current is injected, deflections angle of test subject will be between different polarity will differ between the range of 0 o .Finding of the research prove can GVS application is more suitable to be apply for a momentary usage rather than long duration application. However, GVS can still be applied to visual impaired person but if and only if the navigation is within a small range of distance. o o to 9.67